Translating the English Bible from relevance to deconstruction - Goodwin, Philip W. (Cambridge : James Clarke & Co., 2013)
In his detailed and thought-provoking work, Philip Goodwin conducts a thorough analysis of the challenges facing the Biblical translator, with particular focus on the problematic dominance of the King James Version of the Bible in our imaginations - a dominance which has had a deleterious effect upon the accuracy and originality of the translator's work. Goodwin considers the first two chapters of the Lukan narratives in depth, comparing and contrasting a breadth of widely disparate translations and drawing on a rich body of Biblical scholarship to support his thesis. A wide-ranging discussion.
Clues arising from phonetic propertiesClues arising from semantic constraints on relevance; Clues arising from formulaic expressions; Clues arising from onomatopoeia; Clues arising from the stylistic value of words; Clues from sound-based poetic qualities; Are there other clues?; Uses and abuses of communicative clues; Chapter Six: Repetitive texture and four kinds of literalism; Repetitive texture; Repetitive texture in translation; Concordance: a non-topic?; Concordance and literalism; Four motivations for literalism; The perfect translation; Final remarks: The experimental translation.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Bible -- Translating -- History; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books